DnaJ, DnaK, and GrpE heat shock proteins are required in oriP1 DNA replication solely at the RepA monomerization step. - Wickner, S (1992)
We have found that three Escherichia coli heat shock proteins, DnaK (the hsp70 homolog), DnaJ, and GrpE, function in oriP1 DNA replication in vitro solely to activate DNA binding by the replication initiator protein RepA. Activation results from the conversion of P1 or P7 RepA dimers to monomers that bind with high affinity to the origin of replication of plasmid P1. Thus, the essential role of these three heat shock proteins in this replication system is to change the quaternary structure of a single protein, RepA.